Use of Instagram® to Educate Adolescents on Nutrition Labelling: A Feasibility Study in Selangor, Malaysia - Jefrydin, Norsakira; Mohd Sedik, Farha Shazira; Kamaruzaman, Nurul Anisah; Md Nor, Norazmir; Shapi’i, Azrulhizam; Abd. Talib, Ruzita (Jurnal Gizi dan Pangan, 2020)
This study was undertaken to assess the demand and acceptance of an Instagram-based nutrition labelling education (Info-Nutriteen®) among adolescents. In this quasi-experimental study, a series of educational messages was developed and was uploaded on Instagram for 12 weeks. Participants were recruited and randomized into the intervention group or control group. Feasibility was assessed through participants' demand and acceptance of the program. Changes in nutrition knowledge and Knowledge, Attitudes, and Practices (KAP) on nutrition labels were measured at pre- and post-intervention. A total of 125 participants completed the program. Overall, 92.7% of the participants reported positive acceptance towards Info-Nutriteen®. In terms of demand, they suggested using current and trending songs for the videos and bright colours for the info-graphics. The study showed good demand and acceptance of the Instagram based education for adolescents. The Info-Nutriteen® program also effective to improve their attitude and practice on nutrition labels. Thus, this approach is feasible. Nevertheless, Info-Nutriteen®should be improved further to enhance its impact on nutrition labels knowledge and usage among adolescents.